ASSESSMENT OF IRRIGATED SOILS BY THE LEVEL OF DEFLATION SUSCEPTIBILITY (Web of Teachers: Inderscience Research, 2024)
This article presents the results of monitoring various deflation processes on irrigated lands in the districts of the Jizzakh region, as well as the results of determining the level of risk of deflation in soils.